Association Between Neopterin Levels and Outcome in 30 Day HIV/AIDS Naive Patients - Juanita, Lydia; Hadi, Usman; Arfijanto, Vitanata (Biomolecular and Health Science Journal, 2019)
Introduction: HIV/AIDS is still a major problem throughout the world even in Indonesia. Some markers can provide information regarding the description of immune activity in HIV/AIDS. Neopterin produced by macrophages as a catabolic result of Guanosine Triphosphate (GTP) is one of them. Neopterin has been widely studied as a prognostic indicator of the course in HIV/AIDS. Until now there have been no studies examine the association between neopterin levels and outcomes in 30 days of HIV/AIDS patients.Methods: A prospective longitudinal analytic study involved 56 samples of HIV/AIDS naive patients from January to April 2019. Serum neopterin levels were measured by the Enzyme Linked Immunosorbent Assay (ELISA) method. Outcome is a living condition or death within the first 30 days of the patient being treated. Discriminant function analysis was used to determine the association between variable and controlling confounding factors using the "R" program. Outputs of p value was significant if <0.05.Results: The average age of the study subjects was 39.7 ± 11 years old with predominantly male gender (71.4%). The median serum neopterin level of the study subjects was 168.13 nmol/L with the lowest levels of 11.78 nmol/L and the highest level of 196.95 nmol/L. Outcomes were grouped live and died, each group at 50%. There was a significant positive association between serum neopterin levels and outcomes in 30 days (p=0.02)Conclusion: Role of neopterin levels still need to be proven as a prognostic factor by evaluating other factors that influence the outcome of HIV/AIDS patients.